2016
DOI: 10.1108/ijpdlm-06-2014-0143
|View full text |Cite
|
Sign up to set email alerts
|

Coordination to manage dependencies between logistics service providers and shippers

Abstract: PURPOSEAlthough it has been suggested that shippers' demands regarding environmental practices appear to have an impact on the environmental work of LSPs, limited attention has been given to environmental practices in the relationships between LSPs and shippers. The purpose of this paper is to explore how dependencies between LSPs and shippers can influence the way in which environmental practices are coordinated in the relationships between them. DESIGN/METHODOLOGY/APPROACHFour dyadic case studies, each consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 41 publications
(67 reference statements)
7
42
0
Order By: Relevance
“…The authors found that the buyer has to increase cross-functional and cross-organizational activities in order to preserve its performance. Regarding the coordination aspects of the environmental practices between shippers and 3PLs, Sallnas (2016) [113] found that 3PLs generally depend on shippers in setting the coordination conditions, but the shippers are subjected to 3PLs to achieve successful environmental practices. Focusing on the environmental awareness, Vieira et al (2016) [114] analyzed the relationship among shippers, 3PLs and carriers in managing green actions.…”
Section: Shipper's Perspectives and Collaborationmentioning
confidence: 99%
“…The authors found that the buyer has to increase cross-functional and cross-organizational activities in order to preserve its performance. Regarding the coordination aspects of the environmental practices between shippers and 3PLs, Sallnas (2016) [113] found that 3PLs generally depend on shippers in setting the coordination conditions, but the shippers are subjected to 3PLs to achieve successful environmental practices. Focusing on the environmental awareness, Vieira et al (2016) [114] analyzed the relationship among shippers, 3PLs and carriers in managing green actions.…”
Section: Shipper's Perspectives and Collaborationmentioning
confidence: 99%
“…Secondly, by investigating both the LSPs and shippers, the paper has been able to view the problem from multiple perspectives. At the intersection of the LSPs and their customers lies great improvement potential for energy efficiency, when the actors collaborate in a long-term commitment on equal footing and work together towards environmental sustainability [50]. Following suit, this paper contributes to the body of knowledge by taking an interactive approach to capacity utilisation and presenting multiple interpretations of energy efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Many causes, such as inflexibilities, limited information sharing, and compromises, which lead to inefficiencies for at least one actor, resulted from the relationship between the actors. Sallnäs [50] described those dependencies between the LSPs and the shippers, and stated that if both parties had high environmental ambitions for their relationship, then the coordination of their environmental practises became more likely. This was confirmed through the interviews, however, the responsibilities were too-often eschewed and forwarded to another actor.…”
Section: Key Contributionsmentioning
confidence: 99%
“…Commonly, a positive cooperation strategy of stakeholders will significantly improve the operational performance of G&SL [76] and even the entire supply chain [19]. Therein, the benefits brought by the collaboration between suppliers and customers [77] and LSPs-shippers [78] are particularly salient. The government plays a dominant role in the knowledge dissemination [79] and economic incentive of greenization [20], leading to the innovation of logistics technology.…”
Section: Planning Policy and Management Research Of Gandslmentioning
confidence: 99%